ECLECTIC STYLE AT THE HOUSE OF HERITAGE INTERIOR BATIK KERIS - Purnomo, Agus Dody; Lestari, Indah Puji; Narwastu, Lira Angger (Jurnal Arsitektur ZONASI, 2023)
The Eclectic Style is a combination of more than one architectural and design style from various eras. Although the style is a combination, but it has a unique and beautiful appearance because it is well organized. Likewise, what is contained in the interior design of the Heritage House of the Batik Keris. One of the heritage buildings in Surakarta, which is currently being restored with an adaptive reuse strategy. This century-old building is represented with a different function compared to its previous function. The façade of the building is fresher and the interior arrangement is also unique. The purpose of this study was to examine the implementation of the Eclectic style in the interior of the Heritage House of the Batik Keris. The research method uses the descriptive analysis method. The Heritage House of the Batik Keris or often called 'Omah Lowo' was founded in 1920. The building was originally a residential house and then converted (adaptive reuse) as a batik gallery building, Nusantara craft center, and cafe. Alterations to heritage buildings are minimal, even physically maintained, change is only strengthening. The existence of history is still well tracked and documented through heritage buildings. Heritage buildings can also be a potential for economic development through tourism.